Are there meaningful changes in the performance of professional soccer teams from the first half of the match to the second? Evidence from the data of eight consecutive seasons of the Chinese Super League - Feng, L.; Chmura, P.; Liu, H. (International Journal of Performance Analysis in Sport, 2024)
In the aim to better understanding the dynamic of performance changes between the first and second halves of professional soccer teams, statistics of 1899 matches from 2012 to 2019 of the Chinese Super League (CSL) were collected and analysed. The generalised mixed linear modelling was used to estimate the mean change of each of 40 physical and technical performance-related parameters of soccer teams from the first half of the match to the second, controlling the effects of match status, match location, team strength and opponent strength. Results showed that, out of the selected 40 parameters, only goals (first half vs second half M ± SD: 0.60 ± 0.76 vs 0.82 ± 0.92, ES; ±99% confidence limits: 0.21; ±0.05), shots (5.7 ± 2.8 vs 6.8 ± 3.3, 0.34; ±0.05), individual possession in the attacking third (55 ± 21 vs 62 ± 25, 0.31; ±0.05), cross (9.7 ± 4.6 vs 10.9 ± 5.8, 0.24; ±0.06) and yellow cards (0.75 ± 0.84 vs 1.24 ± 1.07, 0.45; ±0.06) showed substantially increment from the first half to the second, other parameters presented only trivial changes. Hence, it is concluded that the physical performance of soccer teams in the second half did not show meaningful change, while technical actions related to attacking tended to increase. The findings can offer soccer coaches valuable insights into when and how to adjust their tactics, manage their players, thus can maintain or enhance the team`s match performance.